Experimental research on heat transfer characteristics of a two-layer corium pool based on a three-dimensional ellipsoidal lower plenum - Wu, Shihao; Zhang, Yapei; Yu, Jian; Bai, Jingyuan; Tian, Wenxi; Qiu, Suizheng; Su, G. H. (Frontiers in Nuclear Engineering, 2025)
To better understand the application of IVR (In-Vessel Retention), extensive experiments have been conducted on the heat transfer characteristics of molten pool. However, most research mainly focuses on hemispherical lower heads, and the research on ellipsoidal lower head suitable for small pressurized water reactors is relatively lacking. In order to provide some reference for the implementation of IVR with ellipsoidal lower head, this paper conducted the experimental study on the heat transfer characteristics of a three-dimensional double-layer molten pool based on the design of a small pressurized water reactor. The test section consists of two parts: ellipsoidal and cylindrical, with a span of 1150 mm and a total height of 700 mm. The molten material is simulated by nitrate mixture (20mol%NaNO3-80mol%KNO3), and electric heating wire is chosen to simulate the oxide layer decay heat. The effects of heating power, oxide layer height and layered partition thickness on heat transfer characteristics of two-layer molten pool under static conditions were studied. The results show that the thermal stratification phenomenon mainly occurs in the lower and middle regions of the oxide layer, with a smaller dimensionless temperature gradient in the upper region; with the similar volumetric power densities, the height of the oxide layer has little effect on the wall heat flux density; the layered partition increases the thermal resistance between the two layers and reduces the upward heat transfer to the ceramic pool. In addition, the heat transfer relationships in the oxide layer, both downward and upward, are fitted for the internal Rayleigh number range of 3.43 × 1012 to 1.54 × 1013.